Sosialisasi Pencegahan dan Penanganan Kekerasan Seksual pada Remaja di SMP Negeri 2 Satap Konawe Selatan - Yuhanah, Yuhanah; Mutmaina, Rizka (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
The era of disruption has significantly influenced adolescent behavior in Indonesia, particularly regarding sexual violence. This issue leads to physical and psychological suffering, including reproductive health disorders, and diminishes the opportunity for safe and optimal education. In 2021, there were 11,952 cases of sexual violence against children, with 7,004 reported. In Southeast Sulawesi, 240 cases were recorded in 2020, with 35 more by May 2022. Southern Konawe district saw 13 cases. Notably, there was no education on sexual violence at SMP Negeri 2 Satap Konawe Selatan, prompting the lecturer team to conduct community service through socialization. This activity at SMP 2 Satap involved 70 students, aiming to increase adolescent knowledge about sexual violence and establish cross-sectoral partnerships in health, supporting the Ministry of Education and Culture's strategy for a healthy and smart generation. The program used lectures, discussions, and evaluations with pre- and post-tests. Results showed an increase in prevention knowledge from 30% to 79% and understanding of case handling from 20% to 75%, alongside positive feedback from the teacher council. Building a healthy and safe school environment fosters student independence, emphasizing the importance of the Prevention and Handling of Sexual Violence (PPKS). Religion and family also play crucial roles in securing a bright future for adolescents.